PENGARUH EKSTRAK BUAH MENGKUDU (MORINDA CITRIFOLIA) TERHADAP KADAR KOLESTEROL TOTAL DARAH PADA TIKUS PUTIH (RATTUS NORVEGICUS) JANTANGALUR WISTARYANG DIBERI DIET TINGGI LEMAK - Priadna, Astrid Ika; Adiwinoto, Budiarto; Handajani, Fitri (Jurnal Ilmu Kesehatan dan Kesehatan, 2019)
Background: High cholesterol dietinduced hypercholesterolemia. Noni fruit extracthas flavonoids which are expected to reduceblood total cholesterol levels.This study aims to determine the effect of noni fruit extract (Morinda citrifolia) on total blood cholesterol levels in wistar strain male rats (Rattus norvegicus) given a high-fat diet. Method: Experimental study using post test only control group design. A total of 24 wistar strain male rats were divided into 3 groups: negative controlgroup given standard feed; positive control group of experimental animals who were given a high-fat diet; the experimental group treated with a high-fat diet for 14 days and given noni fruit extractat a dose of 200 mg / Kg BB. On the 29th day total blood cholesterol levels were measured for all groups of experimental animals. Results: The Mann Whitney UTest showed a significant increase in total blood cholesterol levels in the positive group of experimental animals given a high-fat diet (68.13 mg/dl) compared to the negative control group of experimental animals given standard feed (51.25 mg/dl). There was a significant decrease in total blood cholesterol levels in the experimental group treated with a high-fat diet and noni fruit extract (61mg/dl) compared to the average positive control group of experimental animals given a high-fat diet (68.13 mg/dl). Conclusion: Provision of a high-fat diet in wistar strain male ratscan significantly increase total blood cholesterol levels. The administration of noni fruit extract in wistar strain male ratscan significantly reduce total blood cholesterol levels